Virtual reality and 360º video in business and institutional communication - Herranz de la Casa, José María (2019)
Addressing the presence and development of virtual reality in the professional field is a somewhat complex challenge. It is a current topic in multiple forums and an emerging field, but it has not consolidated a solid theoretical and academic basis on which to base its presence in society, as well as its possibilities in relation to the construction of storytelling, a new look and business models. This article explains the communicative use of virtual reality in the business and institutional spheres. It is proposed through a representative review of case studies the uses of the multimedia format with immersive capacity and virtual reality developed by some institutions, in order to delimit their intentionality to raise awareness, educate, entertain, inform or develop marketing strategies. In the same way, it describes if this format is only a fashion or a strategy to achieve presence of branding.